RESILIENSI MASYARAKAT DALAM MENGHADAPI BANJIR ROB DI KELURAHAN BANDARHARJO KOTA SEMARANG (Studi Kasus Aspek Lingkungan dan Kesehatan) - Yuniar Widya Larasati; Suhartono Suhartono; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Tidal flood is a familiar phenomenon in the city of Semarang in which sea waters enters the land areas with a level lower than sea level. Kelurahan Bandarharjo is one of the areas in northern area of Semarang that are often exposed to tidal floods and have a high level of severity. Tidal flood in the area will impact on the damage to facilities and infrastructure (water, waste management, drainage, sanitation) as well as the environmental degradation that is characterized by declining quality of public health. Given the vulnerability of society to the negative impact of tidal floods, but the community still survive and choose to stay in the area and the population is increasing through the years. Community resilience can be seen from several aspects, namely economic, social, infrastructure, and health. The purpose of this research is to find out the resilience index of Kelurahan Bandarharjo. This type of research is observational descriptive with Cross Sectional approach, sample in this research is 92 residents of RW 01 Kelurahan Bandarharjo. The result of research shows that 95.7% have high social resilience index, 52,2% of respondents have high resilience index of infrastructure. The conclusion of this research is, the average respondents have medium infrastructure resilience index and has high social resilience index.